Analisis Penerapan Sistem Informasi Manajemen Rumah Sakit (SIMRS) Dengan Pendekatan HOT FIT: Systematic Literature Review - Riyan Putri Kumorowani; Dety Mulyanti (Universitas Katolik Widya Karya Malang, 2023)
HIMS as a series of activities that cover all hospital health services at all administrative levels that can provide information to managers for the management process. In carrying out the hospital management information system process, the HOT FIT method is needed. The HOT FIT method is a complete solution that is most suitable for current difficulties or limitations. The purpose of this literature review is to find out how to analyze the application of a hospital management information system using the HOT FIT method. The literature used in this study is to determine the articles that match the inclusion criteria. The data base used is Google Scholar. The year of publication of literature sources taken is the last 5 years between 2018 and 2023, literature sources use English or Indonesian. The results of 5 articles obtained that the analysis of the application of hospital management information systems using the HOT FIT method is by implementing Human (System use, user satisfaction), Organization (Structure, environment), Technology (system quality, information quality, service quality). It can be concluded that the quality of a management information can be assessed from the level of accuracy and level of relevance of the information data. With the HOT FIT method, information can be more relevant and accurate and this information has benefits for its users. It is also Vnecessary for the hospital to improve the quality of the information management system by paying attention to the stages and models used.